2019
DOI: 10.3390/ijerph16101684
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Caregivers’ Satisfaction with the Management of Children with Autism Spectrum Disorder: A Study at Multiple Levels of Health Care

Abstract: Background: Caregivers are the initial gatekeepers in the health care management of children with autism spectrum disorder (ASD). Methods: This cross-sectional study aimed to determine the factors associated with caregivers’ satisfaction with different levels of health care services in managing children with ASD in Kelantan. The satisfaction scores of 227 main caregivers of confirmed ASD children were assessed with a modified Parent Satisfaction Scale (PSS) questionnaire. Results: The analysis showed that care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Likewise, an early diagnosis can significantly influence parents' responses and enable them to better cope with their children's conditions. 37,38 Similarly, the parents of children who had attended two SLT sessions per week reported considerably better satisfaction levels, which could be attributed to the improvements noted in their children's conditions-a finding consistent with that of Adib et al 31 In a study conducted on ASD children who have speech sound disorders, the greatest improvement was observed when the children received an average of 2.57 SL sessions per week for a period of 6 weeks. 39 Intensive interventions can also improve communication and daily social skills, thereby resulting in ASD children's improved social behaviors.…”
Section: Factors Associated With Parents' Levels Of Satisfaction With...supporting
confidence: 75%
See 1 more Smart Citation
“…Likewise, an early diagnosis can significantly influence parents' responses and enable them to better cope with their children's conditions. 37,38 Similarly, the parents of children who had attended two SLT sessions per week reported considerably better satisfaction levels, which could be attributed to the improvements noted in their children's conditions-a finding consistent with that of Adib et al 31 In a study conducted on ASD children who have speech sound disorders, the greatest improvement was observed when the children received an average of 2.57 SL sessions per week for a period of 6 weeks. 39 Intensive interventions can also improve communication and daily social skills, thereby resulting in ASD children's improved social behaviors.…”
Section: Factors Associated With Parents' Levels Of Satisfaction With...supporting
confidence: 75%
“…In this study, almost two-thirds of the parents reported that their children were diagnosed with ASD at an average age of less than 4 years, matching the findings of different studies. 29,30 This age is considered early compared with those found in other studies [31][32][33] . Notably, parents who received an early diagnosis of ASD for their children (less than 4 years old) had significantly higher levels of satisfaction with the SLS provided than those whose children were diagnosed at later ages.…”
Section: Factors Associated With Parents' Levels Of Satisfaction With...mentioning
confidence: 98%
“…In this study, main caregivers were defined as either fathers or mothers who were mainly responsible for caring and providing the needs for their children with ASD and who were the main people responsible for caring for the child and who were actively engaged in providing care and the needs of the child [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…The dynamic nature of the challenges faced by caregivers of children with ASD puts them at a greater risk for a negative quality of life (QoL). When the diagnosis of ASD is initially made, caregivers have to learn to accept, adapt, and cope with new information and needs [ 11 ]. When the child reaches the ages between four and eight-years-old, caregivers are challenged with new co-morbidities and the child’s increased levels of emotional or behavioural symptoms [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Past I/DD research also demonstrated that the lack of available treatments was a barrier to service use (Brown et al, 2018;Heller et al, 2018;Samuel et al, 2012). While past research documented parental frustration with the availability and accessibility of services for children with disabilities (Nik Adib et al, 2019;Vohra et al, 2014), we know little about the differences in service navigation by older compound and noncompound caregivers. Even in life-limiting conditions without known cures, social convention seeks out supports to improve health and well-being (LaDonna et al, 2017).…”
Section: Discussionmentioning
confidence: 99%